State Sovereignty and Refugee Protection Heribertus Untung Setyardi - Untung Setyardi, Heribertus (Wacana Hukum, 2022)
State sovereignty is often used by some countries as a shield to refuse refugee arrivals and provide protection to them. This is felt detrimental to refugees, even though the original nature of the absolute and exclusive sovereignty of the state can no longer be maintained. In this connection, this paper would like to explain the ideal attitude that countries need to have and take towards refugees so that the international protection goals for refugees can be achieved. This paper is part of the results of the research (dissertation) of the writer who uses the normative legal research method with a conceptual approach.